Left Atrial Spontaneous Echo Contrast and Ischemic Stroke in Patients Undergoing Percutaneous Left Atrial Appendage Closure - Wang, Binhao; Wang, Zhao; Fu, Guohua; He, Bin; Wang, Hangxuan; Zhuo, Weidong; Zhang, Shengmin; Chu, Huimin (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Spontaneous echo contrast (SEC) in the left atrium (LA) is frequently observed in atrial fibrillation (AF) patients and may lead to thromboembolic events. We aimed to investigate both periprocedural and long-term stroke risks associated with LA SEC in AF patients undergoing percutaneous left atrial appendage closure (LAAC). Methods: A total of 408 consecutive AF patients treated with LAAC between March 2015 and February 2019 was divided into two groups based on preprocedural transesophageal echocardiography: the study group (moderate/severe LA SEC; n=41) and the control group (none, mild, or mild to moderate LA SEC; n=367). To attenuate the observed imbalance in baseline covariates, a propensity score matching technique was used. Results: No periprocedural stroke/transient ischemic attack (TIA) was documented. The incidence of device-related thrombus was higher in the study group than in the control group (8.8% vs. 1.3%; P=0.025). The mean follow-up period was 3.2±1.1 years, during which 8 patients (2.2%) in the control group and 4 (9.8%) in the study group experienced stroke/TIA (P=0.024). Moderate/severe LA SEC was identified as an independent predictor of stroke/TIA in both the original population (HR=5.71, 95% CI 1.47-22.19, P=0.012) and the matched population (HR =9.79, 95% CI 1.44-66.86, P=0.020). Conclusions: LA SEC did not show a relationship with periprocedural stroke events in patients undergoing percutaneous LAAC. However, moderate/severe LA SEC increased the incidence of device-related thrombus and the risk of late stroke/TIA.